Estimation of phenolic conjugation by colonic mucosa. - Ramakrishna, B S (1989)
Conjugation of phenol by the colonic mucosa was assessed in vivo using dialysis tubing containing 1.5 ml of 1 mmol/l acetaminophen (paracetamol) and 10 mmol/l butyrate. These were allowed to equilibrate in the rectum for one hour. The glucuronidated and sulphated conjugates of acetaminophen were measured by high pressure liquid chromatography and bicarbonate concentrations by gas analysis. In 21 subjects without colonic disease sulphate conjugation was observed in all cases, with a mean (SE) of 3.86 (0.66) nmol/hour, while glucuronide conjugation was found in seven of 21 cases. Mean (SE) bicarbonate output of 42.9 (3.9) mumol/hour (n = 21) indicated healthy colonic mucosal metabolism and phenolic sulphation in dialysate and agreed with published sulphation rates obtained with cultured cells of colonic epithelium. Acetaminophen sulphation suggests that the colonic mucosa has an important role in the conjugation of phenols, and the method reported here would be useful in assessing the detoxification capacity of the colonic mucosa in diseases of the rectal mucosa.